Students’ Experiences during Pandemic: Basis for Sustainable Educational Practices - Jergen Jel C. Labaria, Karen Salve M. Maute, (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Over a billion students around the world had been impacted by the pandemic. Hence, this study investigated the students’ experiences during the pandemic.The study answered the research question: How do student leaders describe their experiences with the instruction of their universities in the new normal? In this study, the researchers used a qualitative research method design. Purposive sampling technique and convenience sampling were employed to select the respondents from different universities. Interview and observation were also utilized in this study to establish the student leaders’ perception and experience of the existing medium of instruction in their respective universities. Most students preferred modular learning over e-learning; however, due to distance, the teachers could not explain more about the particular topic.The participants further express that aside from having distractive learning environment, they have the feeling of being forced into an enclosed unfamiliar sphere. Their learning environment is not conducive and distractive.their teachers were not responding to their queries, not teaching and giving explanations, and sometimes, they cannot be reached. Although many of the teachers have adjusted accordingly to new forms of communication, few notable ones were unreachable and not felt by students. majority of the participants have positively expressed that their teachers have consistently given them feedback on their output.The sustainability of instruction of state universities in MIMAROPA in the new normal can be highlighted through the adjustment of both instructors and learners have gone through. Based on the findings of the study, the researchers concluded thatthe qualitative method of research revealed the experiences of student leaders during the time of new normal setting such as consideration and empathy, convenience and adequacy, adjustment and distraction, level of responsiveness, and giving feedback in sustainability of instructions in SUC’s in MIMAROPA in the new normal towards a new model.